The complete plastid genome sequence of Lysidice brevicalyx (Fabaceae: Detarioideae), an arbor species endemic to China - Jian-Xin Li; Ying Meng; Ze-Long Nie; Tie-Yao Tu (Mitochondrial DNA. Part B. Resources, 2023)
The plastid genome of Lysidice brevicalyx was successfully assembled using Illumina sequencing reads for the first time. The complete plastid genome of L. brevicalyx is a circular structure of 159,084 bp with a GC content of 36.4%. It comprises a large single-copy (LSC) region of 87,783 bp, a small single-copy (SSC) region of 19,557 bp, and two inverted repeat regions (IRA and IRB) of 25,872 bp, each. The plastome of L. brevicalyx contains a total of 128 genes, including 83 protein-coding genes, 37 tRNAs, and 8 rRNAs. The phylogenetic analysis strongly supports the monophyly of Lysidice. This study provides the first complete plastid genome sequence of L. brevicalyx and contributes to our understanding of the molecular characteristics and evolutionary relationships of this plant species.